James Houston Henderson papers - Henderson, James Houston, 1878-1935.
Correspondence, employment records, biographical notes, and photographs chiefly relating to Henderson's work as chief surveyor of the Panama Canal and as a civil engineer for the construction of roads and bridges for the Panama Railroad. Includes Henderson's letters to his wife, Lula Ross Henderson.
Surveyor and civil engineer.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Henderson, Lula Ross -- Correspondence; Panama Railroad Co; Bridges -- Design and construction; Civil engineering -- Panama; Railroads -- Panama; Roads -- Construction -- Panama; Surveying -- Panama; Panama Canal (Panama) -- Surveys; Civil engineers; Surveyors